2009
DOI: 10.1088/0953-4075/42/23/235207
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical (e, 2e) studies of formic acid

Abstract: We present triply differential cross sections for the electron impact ionization of the outer valence orbitals of formic acid (CHOOH) by 100 eV and 250 eV incident electrons. The experiments were performed under asymmetric kinematics, in which the outgoing ejected electron had an energy of 10 eV, over a range of momentum transfers. The experimental results are compared with theoretical calculations carried out using the sophisticated M3DW model, both with and without correlation-polarization-exchange terms inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 47 publications
2
26
1
Order By: Relevance
“…Comparably broad binary peaks have also been observed in experimental studies for molecules including water, 57 formic acid, 52 methane, 58 and nitrogen 59 under similar kinematics. Broad binary peaks were also observed for TDCS measurements of the HOMO of THF.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Comparably broad binary peaks have also been observed in experimental studies for molecules including water, 57 formic acid, 52 methane, 58 and nitrogen 59 under similar kinematics. Broad binary peaks were also observed for TDCS measurements of the HOMO of THF.…”
Section: Resultssupporting
confidence: 60%
“…We previously suggested that the small recoil peak intensity observed for some molecular targets, in particular CHCOOH and THF, relative to H 2 O was due to the lack of a charge center at the molecule's center of mass. 24,52 An alternative explanation has been proposed by Xu et al, 53 which is that rather than being related to the geometry of the target this observation more simply results from the momentum profile of the orbitals investigated and the kinematics being close to the Bethe ridge. Following from this argument, as a consequence of the momentum profile of the HOMO of THFA having non-zero intensity at zero momentum (see Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Indeed, this kinematical condition has been most interesting in terms of our earlier dynamical (e,2e) studies on large biomolecules. [8][9][10][11][12][13][14] …”
Section: Experimental Methodsmentioning
confidence: 99%
“…Such studies represent an important step in understanding how the structure of a species can influence the electron scattering phenomena. In this vein, we have recently extended some of our earlier studies on individual biomolecules [8][9][10][11][12][13][14] to chemically similar compounds in an attempt to further understand the role of structure and kinematics on the dynamics of electron-impact ionization. 15 Building on that work, we present a dynamical (e,2e) investigation to compare the electron-impact ionization process across a series of cyclic ethers: tetrahydrofuran (THF, C 4 H 8 O), tetrahydropyran (THP, C 5 H 10 O), and 1,4-dioxane (C 4 H 8 O 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, while there has been an increased interest in these studies over the last decade, both theoretical and experimental studies have mostly been limited to smaller targets. Recently, molecules including methane 14,15 and formic acid 16 have been investigated. Studies concerning larger molecules such as component molecules of DNA and RNA are rare, and include tetrahydrofuran 17 and theoretical studies on thymine.…”
Section: Pyrimidine (C 4 H 4 N 2 )mentioning
confidence: 99%